PARENT APPROACH AND AVOIDANCE TEMPERAMENTS AND PARENTING BEHAVIORS: CHILD BEHAVIORS AS MODERATING MECHANISMS - Duchesne, Stéphane; Boisclair-Châteauvert, Geneviève (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2025)
Parents’ temperaments are assumed to be involved in their parenting behaviors, but empirical evidence is limited. Using self-determination theory (SDT) as a guiding framework, this study examined the associations between parents’ approach and avoidance temperaments and parenting behaviors over a 7 month period. Children’s manifestations of inattention and prosociality were explored as moderators. A sample of 101 parents (79% mothers) with a child in Grade 4 or Grade 6 participated in this study. Findings indicate that approach temperament positively predicted autonomy-supportive and structuring behaviors, while avoidance temperament positively predicted controlling behaviors. Distinct association patterns were also observed for involvement and structure depending on the children’s behavioral characteristics: approach-oriented parents were more likely to engage in structuring behaviors with low prosocial and highly inattentive children. Moreover, avoidance-oriented parents, although less likely overall to employ structuring behaviors, were also more prone to adopt those behaviors when engaging with low prosocial children. Results suggest that SDT-based parenting responses (autonomy support, structure, involvement) as well as controlling responses to children’s behaviors may be driven by parents’ approach and avoidance dispositions. Implications for theory, research, and the prevention of negative parenting behaviors are presented.